2006
DOI: 10.12968/bjon.2006.15.17.21906
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care delivery in Japanese psychiatric units

Abstract: Japan has the largest number of psychiatric beds per population in the world. At the same time, little research had been done to describe nursing care delivered in psychiatric units. To describe contents of nursing care, the framework for care classification and measuring methods must be examined. The purpose of this study was to develop a nursing intervention classification and examine the correlation between amount of care and patients' mental states. Data were collected from 39 patient care records from 4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These domains and items were reviewed by a working group that included researchers and practitioners from a psychiatric hospital. The domains were developed based on categories of the psychiatric nursing intervention classification system in Japan [ 21 ]. The items were intended to cover a variety of discharge planning [ 22 ], the concept of the therapeutic nurse-client relationship [ 23 ], and family involvement [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…These domains and items were reviewed by a working group that included researchers and practitioners from a psychiatric hospital. The domains were developed based on categories of the psychiatric nursing intervention classification system in Japan [ 21 ]. The items were intended to cover a variety of discharge planning [ 22 ], the concept of the therapeutic nurse-client relationship [ 23 ], and family involvement [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A Japanese study (Sawada et al . ) documented a significant correlation between the amount of care provided and patients’ mental states. The patients’ mental states were measured using two validated scales: the GAF scale (Global Assessment of Functioning) (American Psychiatric Association ), which is used to assess the psychosocial and professional performance of patients, and the BPRS (Brief Psychiatric Rating Scale) (Overall & Gorham ), which is used to provide a measurement for identifying patients’ dysfunctional attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Sawada et al [31] reported that the roles of psychiatric nursing care as "basic activities of daily living, psychological support/interpersonal skills, medical support, monitoring, family support and miscellaneous" may be required interventions for patients in acute psychiatric hospitals in Japan.…”
Section: Discussionmentioning
confidence: 99%